Artikel Review: Metode Analisis Kuantitatif Bahan Merkuri (Hg) dalam Produk Pemutih Kulit (Body Lotion) menggunakan Spektrofotometri Serapan Atom (SSA) di Indonesia - Andina, Cantika; Salsabila, Fannysa; Muzaqil, Firmansyah; Senja Maelaningsih, Firdha (LP4M STIKes Karsa Husada Garut, 2024)
Introduction: Heavy metal mercury is often used in cosmetic products such as body lotion to help speed up the skin whitening process. Cosmetics containing mercury can cause side effects such as skin disorders, cancer, and nervous system poisoning. The purpose of this study is to provide information to readers about research that analyzes mercury content in body lotion products using Atomic Absorption Spectrophotometry (AAS) in several regions of Indonesia. Method: This research method is a literature study involving online article searches from 2014 to 2024 in the Google Scholar database. Results: The results of five article reviews showed the presence of mercury in body lotion product samples. Conclusion: in several regions of Indonesia mercury with the highest concentration of 39.51 mg/kg in Mataram and the lowest 0.051 ppb in Banda Aceh. The majority of products identified as positive do not have a permit from BPOM and are sold freely in the market or online. Therefore, strict supervision of the distribution of cosmetics is needed to protect the public from health risks caused by mercury (Hg). Keywords: Quantitative analysis, body lotion, mercury, atomic absorption spectrophotometry (AAS)